TI_GERICHTE 52.2017.546 vom 27. Januar 2016 , Licenza edilizia per l'edificazione di due nuove case unifamiliari - TI Tribunale d'appello (2016)
Licenza edilizia per l'edificazione di due nuove case unifamiliari